Baseline albuminuria predicts the efficacy of blood pressure-lowering drugs in preventing cardiovascular events - Boersma, Cornelis (Blackwell Science Inc, 2008)
AIMS: Albuminuria has been proven to be associated with cardiovascular (CV) events in specific patient populations, but also in the general population. This study aimed to investigate whether the efficacy of blood pressure-lowering agents in preventing CV events depends on baseline urinary albumin excretion (UAE) and, if so, whether this holds true for blood pressure-lowering agents in general, or is limited to agents that interfere in the renin–angiotensin system. METHODS: Data were used from a community-based cohort study and pharmacy dispensing records. Included were subjects with hypertension (systolic blood pressure ≥140 and/or diastolic blood pressure ≥90 mmHg), no cardiovascular disease history, and no previous use of blood pressure-lowering agents. RESULTS: During study follow-up (7.1 ± 1.6 years), 122 CV events were observed in 1185 subjects included. Start of blood pressure-lowering agents vs. non-use was associated with a difference in absolute CV event risk of 0.7%, 6% and 12.6% for all subjects, those with UAE ≥ 15 mg day(−1) and ≥30 mg day(−1), respectively. Cox regression analysis showed that the relative risk for CV events after start of blood pressure-lowering agents was significantly dependent (P < 0.05) on baseline UAE; with hazard ratios of 0.87 [95% confidence interval (CI) 0.48, 1.60, P = NS], 0.58 (95% CI 0.36, 0.94, P < 0.05) and 0.37 (95% CI 0.20, 0.68, P < 0.05), for subjects with UAE < 15, ≥15 and ≥30 mg day(−1), respectively. Results adjusted for covariates were essentially similar. The use of angiotensin converting enzyme inhibitor/angiotensin-II receptor blocker (ACEi/ARB) treatment tended to be associated with a more favourable CV prognosis when compared with non-ACEi/ARB treatment (difference P = 0.06). CONCLUSIONS: Our results suggest that the efficacy of blood pressure-lowering agents to prevent CV events is dependent on baseline albuminuria. The higher baseline albuminuria, the more absolute as well as relative risk reduction can be achieved. Our data suggest that this may especially be true for ACEi/ARBs. We caution that this is an observational study, and that these conclusions should therefore be regarded as hypothesis generating, rather than hypothesis testing.